Attitudes of young consumers at college age towards the purchase of unpackaged goods in the context of the world economy – a case study Czech Republic - Navrátilová Miroslava; Brož David; Beranová Markéta (SHS Web of Conferences, 2021)
Research background: Today, society faces many challenges such as biodiversity loss, water and soil pollution, deforestation and unsustainable production. Responsible waste production and waste management can be instrumental in improving the overall sustainability of the planet. Thus, unpackaged goods are one of the tools available, especially for the young generation, which can be used. The use of the circular economy will be a necessity to maintain a high standard of living especially for the current college age generation. Purpose of the article: The main purpose of this paper is to find out the attitude and opinion of the college age generation towards unpackaged goods, zero waste and general awareness of waste and environment. Unpackaged food is becoming, more and more a sought after standard and especially for young people. Unfortunately, the current COVID 19 crisis has significantly affected alternative ways of selling, led by the concept of unpackaged food. Methods: The contingency tables and χ2 test was used. Findings & Value added: The results show more than 83% of respondents sort waste, with plastics, paper and glass being the most frequently sorted waste. Awareness of the concept of Zero Waste was declared by 90.7% of college age youth. Females demonstrated higher awareness of this issue than males (93.3% vs. 84.1%). The concept of zero packaging in retail was noted by 85.3% of people. Respondents had encountered some forms of zero packaging sales.